Mothers' Attitudes of Health Care for Preterm Neonates Post Discharge from Neonatal Intensive Care Units (NICUs) in Govermental Hospitals in the Gaza Strip, Palestine - AbuMustafa, Dr. Ayman M. (Jour Med Resh and Health Sci, 2020)
Background: Preterm birth is one of most common health problems, associated with neonates admitted to Neonatal Intensive Care Unit (NICU). Globally, every year, an estimated 15 million neonates are born preterm, this number is rising globally as well as in 2015, preterm birth and low birth weight accounted for about 17% of infant deaths and more than one million died due to complications in the first month of life. Mother's attitudes about neonate care influences the nature and quality of care that is given to the preterm. Hence, this study aims to evaluate mothers' attitudes of health caring for premature infants after discharge from NICU in the Gaza Strip. Methods: A Quantitative, cross-sectional design study was used to survey 120 mothers of preterm neonates at the time of discharge by face-to-face interview at Al-Shifa medical complex and Nasser hospital between February and June 2018 Results: The results showed that about 88.3% of mothers of preterm babies had positive attitudes about health care needed for preterm neonates after discharge from NICU. Mothers admitted to Al-Shifa hospital had significantly higher attitudes than who were admitted to Nasser hospital. Furthermore, there was no statistically significant difference between the level of attitudes and mother’s other sociodemographic characteristics (P-values > 0.05). Conclusion: Mothers’ attitudes of preterm neonates care was not at the optimal level, which might put the newborns at risk. Therefore, the study emphasis to maternal education during hospitalization in NICU prior to discharge, certain components of essential preterm care package need more emphasis during education program.